Application of Biological Organic Fertilizers Towards P Dosage Reduction in Shallot Cultivation - Moch. Arifin; Tri Mujoko (Future Science)
With the large need for organic fertilizer in fulfilling agricultural cultivation, vermicompost is a fast and appropriate way to utilize local natural resources in meeting the needs of organic biological agents. This study aims to determine the effect of giving organic fertilizer kascing with biological dimensions and chemical fertilizers (Urea, KCl, KNO3 Merah, and Phonska) with indicators of shallot plants. The study was conducted using a randomized block design, with the treatment of giving biological fertilizer with a dose of 30 tons/ha combined with chemical fertilizer with a dose (Urea 200 tons/ha; KCl 200 tons/ha; red KNO3 200 tons/ha, and Phonska 200 tons / ha Ha). The treatments P0 (without chemical fertilizer), P1 (25% of the dose of chemical fertilizer), P2 (50% of the dose of chemical fertilizer), P3 (75% of the dose of chemical fertilizer) and P4 (100% of the dose of chemical fertilizer). The results showed the availability of P-soil and C-organic soil after treatment were not significantly different. Observation of plant height also shows unreal results. While the number of tubers and production results obtained P2 gives the highest yield and is significantly different from other treatments.